KEKERASAN TERHADAP ANAK; STRATEGI PENCEGAHAN DAN PENANGGULANGANNYA - Dian Ika Aryani; Nila Imtiyaz Elhada (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2021)
: This paper aims to decital and offer alternative measures to prevent child abuse. Through the study of literature with descriptive analytical methods, this paper concludes that violence against children can occur anywhere and involves many factors. The handling of acts of violence against children is carried out in a massif, holistic, comprehensive, and continuous. The involvement of parental awareness, social control, government supervision, social services, medical, and psychologists is necessary to prevent, overcome, and break the chain of violence against children.